The role of advertisements in ESP teaching - Petrovska, Irina (Array, 2008)
Advertisements are used in foreign language teaching, but this genre is appealing as in the ESP classroom as it is in everyday life. This article examines the main arguments for using ads in EFL, as a specific trend in education for tourism and hospitality industry. With reference to recent research, the article focuses on some of the appealing uses of language, culture in advertising, some visual aspects and how language teachers could exploit them in the classroom